2019
DOI: 10.1002/sctm.19-0159
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Neuro-Supportive Properties of Astrocytes with Epidermal Growth Factor Hydrogels

Abstract: Biomaterials provide novel platforms to deliver stem cell and growth factor therapies for central nervous system (CNS) repair. The majority of these approaches have focused on the promotion of neural progenitor cells and neurogenesis. However, it is now increasingly recognized that glial responses are critical for recovery in the entire neurovascular unit. In this study, we investigated the cellular effects of epidermal growth factor (EGF) containing hydrogels on primary astrocyte cultures. Both EGF alone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Thus, our data clearly show that rhFGF21 induces the A2 phenotype, and the observed reduction in the A1 phenotype strongly supports the contribution of rhFGF21 to astrocyte modulation in astrocyte cultures and ischemic brain. Furthermore, A2 astrocytes are now known to play beneficial roles in neuronal survival under pathological conditions [48,13]. After brain damage, A2 astrocytes promote synapse formation, support blood-brain barrier function, and release nutritional factors such as BDNF, Thbs-1, and IGF-1, which have been suggested to be protective in models of stroke [49].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data clearly show that rhFGF21 induces the A2 phenotype, and the observed reduction in the A1 phenotype strongly supports the contribution of rhFGF21 to astrocyte modulation in astrocyte cultures and ischemic brain. Furthermore, A2 astrocytes are now known to play beneficial roles in neuronal survival under pathological conditions [48,13]. After brain damage, A2 astrocytes promote synapse formation, support blood-brain barrier function, and release nutritional factors such as BDNF, Thbs-1, and IGF-1, which have been suggested to be protective in models of stroke [49].…”
Section: Discussionmentioning
confidence: 99%
“…The A2 subtype is associated with a neurotrophic profile with increased levels of BDNF, FGF2 and VEGF to promote CNS repair and regeneration (Gao et al, 2005 ; Zador et al, 2009 ; Hayakawa et al, 2014 ). A2 astrocytes also produce thrombospondins that aid in synapse repair (Chan et al, 2019 ).…”
Section: Astrocyte Phenotype and Glymphaticsmentioning
confidence: 99%
“…In the hope of advancing this area of study, researchers from the laboratory of Eng H. Lo (Massachusetts General Hospital, Boston, Massachusetts, USA) evaluated the influence of EGF‐containing gelatin (Gtn) hydrogels on astrocytes in culture. Writing in Stem Cells Translational Medicine , Chan et al revealed that while EGF and EGF‐hydrogels increased the proliferation of primary rat cortical astrocytes to a similar degree, only the EGF‐hydrogels displayed the capacity to modulate astrocyte activation by shifting gene expression profiles away from the inhibitory A1‐like astrocyte phenotype (expression of Fbln5 and Rt1‐S3) toward the potentially beneficial A2‐like phenotype (expression of Clcf1, Tgm1, and Ptgs2). Further analyses employing conditioned media derived from astrocytes cultured on EGF‐hydrogels revealed the protection of neurons against injury and the promotion of synaptic plasticity after oxygen‐glucose deprivation, thereby providing further evidence that EGF‐hydrogels shift astrocytes into neuro‐supportive phenotypes.…”
Section: Featured Articlesmentioning
confidence: 99%
“…Overall, these findings suggest that in‐depth research into astrocyte biology may foster the development of new means to enhance recovery in the CNS following traumatic injury or neurodegeneration that act synergistically with NSC‐based approaches. In our first Featured Article published in Stem Cells Translational Medicine this month, Chan et al report how epidermal growth factor (EGF)‐containing hydrogels shift astrocytes into a pro‐recovery phenotype; a discovery that may foster the development of enhanced CNS regenerative medicine therapies combining neuron‐ and astrocyte‐based approaches . In a Related Article published in Stem Cells , Dai et al established that neonatal rat astrocytes promoted NSC proliferation to a greater extent than adult rat astrocytes thanks to the overexpression of Tenascin‐C (TNC); can these findings facilitate enhanced neuroregeneration in the damaged brain ?…”
mentioning
confidence: 99%